AMBULATORY BLOOD PRESSURE MONITORING BY A NOVEL CUFFLESS DEVICE: POTENTIAL ROLE IN OVERWEIGHT PATIENTS. (April 2021) - Margonato, Davide; Scalise, Filippo; Gallone, Giuseppe; Fracchioni, Ilenia; Bruni, Fabio; Ballabeni, Cinzia; Mancia, Giuseppe
Abstract : Objective: Inappropriate cuff size can lead to erroneous blood pressure (BP) measurements and, therefore, to misclassification and potential unnecessary treatment; this problem has a particular relevance in overweight patients. We assessed whether a new cuffless BP device was equally effective for BP measurements over the 24 hours compared to a standard oscillatory BP device in overweight patients (BMI >25). Design and method: BP was measured simultaneously by the cuffless (CL-BP, Rooti RX TM) and by a standard device (C-BP, SpacelabsTM, 90207) over the 24 hours in 100 consecutive patients. Calculations included 24 hour mean systolic (S) and diastolic (D) BP and heart rate (HR). Correlations between the CL-BP and C-BP measurements were sought using Pearson's correlation coefficients and Bland-Altman plots. Results: Using the C-BP device, the 24 hour SBP value was 125.4 ± 10.9 mmHg (mean . ± SD); the corresponding DBP value being 75 ± 8.3 mmHg. Mean SBP/DBP with the CL-BP device were 131.1 ± 15.9/80.2 ± 9.7 mmHg. The correlation coefficients between the two sets of values was significant (SBP: r = 0.58, p = 0.006 - DBP: r = 0.65, p = 0.0002). Mean absolute SBP and DBP disagreements between CL-BP and C-BP were 5.7 ± 13.1 mmHg and 5.2 ± 7.7 mm Hg, respectively. In the 54 patients classified as overweight, C-BP mean SBP value was 126.4 ± 10.6 and mean DBP value was 76, 2 ± 8, 5; in the CL-BP device arm SBP was 130 ± 14, 1 and DBP was 80, 9 ± 9, 9. Better SBP and DBP correlations for SBP and DBP was found in patients with BMI > 25 (SBP: r = 0.65, p = 0.13 - DBP: r = 0.70, p = 0.009) compared to those with BMI <25 (SBP: r = 0.52, p = 0.02 - DBP: r = 0.51, p = 0.06). Conclusions: Our results show that a CL-BP device was accurate in estimating 24 hours BP in overweight patients, compared to a classical oscillometric device. Therefore, if confirmed on a larger population scale, CL-BP device could be used to provide accurate standardized BP measurements, independently by the arm size of the patients, and avoid a significant number of BP quantification mistakes.